2015
DOI: 10.3122/jabfm.2015.01.140151
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Myofascial Trigger Point Injections on Nocturnal Calf Cramps

Abstract: Background: The purpose of this study was to elucidate the effects of injection at trigger points on pain and sleep disturbance in patients with nocturnal calf cramps (NCCs).Methods: Patients with NCCs that occurred at least once per week and who had myofascial trigger points (MTrPs) on the gastrocnemius muscles were enrolled in the study for 9 months. At the first visit (T0), we measured the intensity of NCC pain on an 11-point numeric rating scale, recorded the frequency of NCCs, and calculated the Insomnia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Even during the present study, in addition to symptoms such as “back pain” and “frequent urination,” which were believed to be due to geriatric syndrome, symptoms of general malaise such as “cramps”, “numbness in the legs”, and “swelling” and “easy to get foot cramps” appeared frequently. A relationship between diabetes mellitus/hypoglycemia and symptoms such as “cramps” has been reported [ 23 , 24 ]; therefore when asking about hypoglycemia during routine examination, physicians should inquire patients regarding not only the known conventional symptoms of hypoglycemia but also the various symptoms of general malaise shown that many patients have in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Even during the present study, in addition to symptoms such as “back pain” and “frequent urination,” which were believed to be due to geriatric syndrome, symptoms of general malaise such as “cramps”, “numbness in the legs”, and “swelling” and “easy to get foot cramps” appeared frequently. A relationship between diabetes mellitus/hypoglycemia and symptoms such as “cramps” has been reported [ 23 , 24 ]; therefore when asking about hypoglycemia during routine examination, physicians should inquire patients regarding not only the known conventional symptoms of hypoglycemia but also the various symptoms of general malaise shown that many patients have in this study.…”
Section: Discussionmentioning
confidence: 97%
“…(12,13,14,15) Massage has increasingly been used in health care over the past 10 years. Research studies using massage in cancer patients have shown a decrease in pain, increase in energy, decreased inflammation and decreased feelings of anxiety when done appropriately.…”
Section: Intervention Groupmentioning
confidence: 99%
“…In another report, video capability of new phones has led to a practical way to learn and use the particle repositioning maneuver for benign paroxysmal positional vertigo, which is common in family medicine offices. 11 In a brief report Kim et al 12 present the outcomes of myofascial trigger point injections for nocturnal calf cramps among 12 patients; positive results indicate the need for larger randomized trials with appropriate placebo controls.…”
Section: Interventions For the Individual Providermentioning
confidence: 99%